Multiple sclerosis presenting as isolated peripheral facial nerve palsy - Karadan, Ummer; Manappallil, Robin George; Anil, Revathy (Indian Journal of Case Reports, 2019)
Isolated facial nerve palsy is commonly seen with Bell’s palsy. However, it can be associated with a central lesion at the level of the ipsilateral facial nucleus or the facial nerve at the pons. Multiple sclerosis is a chronic autoimmune inflammatory disease characterized by axonal degeneration and demyelination of the central nervous system. Isolated cranial neuropathies are rarely seen with multiple sclerosis. The patient being reported is a 20-year-old female who developed isolated facial nerve palsy, which was initially treated as Bell’s palsy. However, she was found to have multiple sclerosis on MRI brain. Isolated facial nerve palsy due to multiple sclerosis is a rare scenario and can often get misdiagnosed and treated as Bell’s palsy.